2007
DOI: 10.1007/s00431-007-0614-9
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing enterocolitis of the neonate with Clostridium perfringens: diagnosis, clinical course, and role of alpha toxin

Abstract: The severity of the clinical course in necrotizing enterocolitis (NEC) associated with Clostridium perfringens (Cp) may support the hypothesis of a specific disease. We conducted a case control study of infants diagnosed with NEC, who underwent surgical treatment over a 7-year period. Patient histories examined characteristics of the infants, bacterial infection as well as NEC's severity, antibiotic treatment, and clinical course. Infants infected with NEC associated with Cp were compared with NEC patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
56
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 27 publications
4
56
0
4
Order By: Relevance
“…The presence of clostridia is frequently associated with acute outbreaks and more lethal courses of NEC in human infants. 14,18,19,21,27 This was also true of the present study in which all but one piglet with NEC had acute clinical disease and died or had to be euthanized prior to the 30 h endpoint of the study. TRFLP patterns from small intestinal mucosa consistent with Clostridium spp.…”
Section: Discussionsupporting
confidence: 60%
“…The presence of clostridia is frequently associated with acute outbreaks and more lethal courses of NEC in human infants. 14,18,19,21,27 This was also true of the present study in which all but one piglet with NEC had acute clinical disease and died or had to be euthanized prior to the 30 h endpoint of the study. TRFLP patterns from small intestinal mucosa consistent with Clostridium spp.…”
Section: Discussionsupporting
confidence: 60%
“…37 This bacterial species has also been considered as a causal agent of necrotizing enterocolitis in infants. 38 Similarly, a higher prevalence of C. perfringens has been proposed to possibly increase the risk of suffering other chronic intestinal disorders. Altogether, this evidence could support the protective role attributed to breast-feeding in reducing the rate of infections and, in turn, has been related to a reduced risk of developing CD in some studies.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found an association between various bacterial species and NEC (15)(16)(17)(18)(19)(20), whereas others did not observe any association between NEC and any specific bacterial species (8,21).…”
Section: Discussionmentioning
confidence: 99%